Forensic DNA analysis technological development and innovative applications - Pilli, Elena; Berti, Andrea (Apple Academic Press, 2021)
Forensic DNA Analysis: Technological Development and Innovative Applications provides a fascinating overview of new and innovative technologies and current applications in forensic genetics. Edited by two forensic experts with many years of forensic crime experience with the Italian police and with prestigious academic universities, the volume takes an interdisciplinary perspective. It presents an introduction to genome polymorphisms, discusses, forensic genetic markers, presents a variety of new methods and techniques in forensic genetics, and looks at a selection of new technological innovations and inventions now available from commercial vendors. Key features: Examines the genome polymorphisms and forensic identity markers Presents new scientific and technological developments in forensic genetics Describes the sequencing technology in forensic science in depth Presents the different fields of application of the new sequencing technology Highlights the importance of physical and molecular methods to solve forensic anthropology issues Looks at forensic genetics issues in criminal justice, ancestry, wildlife, entomology, etc. The book is an important resource for scientists, researchers, and other experts in the field who will find it of interest for its exhaustive discussion of the most important technological innovations in forensic genetics. For those newer to the field, the volume will be an invaluable reference guide to the forensic world"-- Provided by publisher.